KEY DETERMINANTS OF GLOBAL LEGAL INSTITUTIONS (PHILOSOPHICAL ASPECT) - Kharchenko, Julia; Kharchenko, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Abstract. It is confirmed that, in the modern global society, a certain general image of legal institutions has been formed, which, being a "superimposed" model adjusts other existing models to suit it. The “legal institution ”performs its classical function for regulating social relations, enshrined in legal acts of various levels. The aim of this study is the explication of "global legal institutions" in the framework of modern socio-philosophical and philosophical-legal discourse and conceptualization of the key determinants of their development. The key task is to comprehend the phenomenon of global legal institutions and its impact on the modern global legal society. The sociophilosophical and philosophical-legal methodological principles made it possible to reveal the connections of global legal institutions with other phenomena of law, to fix the coherence of the formulated and codified legal norms with the basic ideas and moral goals underlying them. It is proved that the key determinants of global legal institutions are: a reflection of the global system of law in terms of its structure, as well as the logic of its development. Global legal institutions can be formed at the junction of various supranational entities, associations, unions, and alliances as a set of legal norms governing relations within these entities. The conclusions prove that the key determinants of global legal institutions are the legal regulation of norms and protocols due to the presence of many global dissimilar legal systems; the asymmetry of the norms of legal liability, where the theoretical and practical models of legal liability often do not correlate due to the complexity of the design of an integral global legal system.